Loss of perceived social role, an index of social frailty, is an independent predictor of future adverse events in hospitalized patients with heart failure - Watanabe, Ayako; Katano, Satoshi; Yano, Toshiyuki; Nagaoka, Ryohei; Numazawa, Ryo; Honma, Suguru; Yamano, Kotaro; Fujisawa, Yusuke; Ohori, Katsuhiko; Kouzu, Hidemichi; Ishigo, Tomoyuki; Katayose, Masaki; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims Although the impact of physical frailty on prognosis and the effect of cardiac rehabilitation in HF patients has been well established, data for the prognostic impact of social frailty (SF) in HF patients are limited. In addition, the relative importance of each SF domain in clinical outcomes remains unclear. We aimed to get a new insight into the associations of SF with clinical outcomes in elderly hospitalized HF patients. Methods A single-center, retrospective cohort study was conducted using data from 310 in-hospital HF patients aged ≥ 65 years (mean age of 78 ± 8 years; 49% women). Makizako’s five questions, a self-reported questionnaire, were used to define SF. The primary outcome was composite events defined by all-cause death and cardiovascular events. Results Of the 310 elderly HF patients, 188 patients (61%) had SF. Seventy-five patients (24%) had composite events during a mean follow-up period of 1.93 ± 0.91 years. Kaplan-Meier curves showed that patients with SF had a significantly higher composite event rate than patients without SF. In multivariate Cox regression analyses, SF was independently associated with a higher composite event rate after adjusting for prognostic markers [adjusted hazard ratio (HR), 2.01; 95% confidence interval (CI), 1.07–3.78; p = 0.04]. Of the 5 questions for defining SF, an answer of yes to the question about not feeling helpful toward friends or family, which indicates loss of perceived social role, was an independent predictor of composite events (adjusted HR, 2.28; 95% CI, 1.36–3.82; p < 0.01). Inclusion of loss of perceived social role into the baseline prognostic model improved both the continuous net reclassification improvement (0.562; 95% CI, 0.298–0.827; p < 0.01) and integrated discrimination improvement (0.031; 95% CI, 0.006–0.056; p = 0.02). Conclusion Loss of perceived social role is associated with increased adverse event risk and provides additive prognostic information in elderly HF patients.